Effect on attendance at breast cancer screening of adding a self administered questionnaire to the usual invitation to breast screening in southern England. Issue 2 (February 1998) - Banks, E; Richardson, A; Beral, V; Crossley, B; Simmonds, M; Hilton, E; English, R; Davis, J; Austoker, J
Abstract : STUDY OBJECTIVE: The primary aim of the research described in this paper was to ascertain whether inclusion of a self administered questionnaire with the usual invitation to routine breast screening affected screening uptake. Secondary aims included establishing appropriate questionnaire distribution and collection methods within the framework of the National Health Service Breast Screening Programme and optimisation of questionnaire design. DESIGN: Randomised study. SETTING: Oxfordshire and West of London Breast Screening Units. PARTICIPANTS/METHODS: 6400 women invited for routine screening mammography were individually randomised to receive either the usual breast screening invitation alone, or to receive the usual invitation accompanied by a self administered questionnaire, to be returned at the time of screening. Participants were then followed up and attendance rates at screening were compared between groups. MAIN RESULTS: Screening attendance rates were similar in women who did and did not receive a questionnaire (71% in each group). Of those who were sent a questionnaire and attended for screening, 77% returned a completed questionnaire. Screening uptake was not affected by the way in which the questionnaire was returned or by whether or not personal details and signed permission for follow up were requested. CONCLUSIONS: The inclusion of a self administered questionnaire accompanying the invitation to breast screening did not adversely affect screening uptake. A high proportion of women completed the questionnaire.